1987
DOI: 10.3181/00379727-184-rc2
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis Caused By Human Rotaviruses (Serotype Three) In A Suckling Mouse Model

Abstract: The pathogenic p o t e n t i a l of human r o t a v i r u s e s of s e r o t y p e s 1 through 4 was e v a l u a t e d i n s u c k l i n g mice. Oral i n o c u l a t i o n of t h r e e d i f f e r e n t human r o t a v i r u s e s of s e r o t y p e 3 i n t o 5-6 day o l d CD-1 mice caused d i s e a s e c h a r a c t e r i z e d by d i a r r h e a and dehydration. The mean 50% d i a r r h e a inducing dose (DD50) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
3
17
1
Order By: Relevance
“…2). This result confirmed that of Bell et al (3), in which serotype 3 human rotaviruses were able to cause gastroenteritis in suckling CD-1 mice. Human serotype 3 strain of rotavirus appears to be serotypically similar to at least one strain (EB) of murine rotavirus, as shown by Greenberg et al (14).…”
Section: Discussionsupporting
confidence: 82%
“…2). This result confirmed that of Bell et al (3), in which serotype 3 human rotaviruses were able to cause gastroenteritis in suckling CD-1 mice. Human serotype 3 strain of rotavirus appears to be serotypically similar to at least one strain (EB) of murine rotavirus, as shown by Greenberg et al (14).…”
Section: Discussionsupporting
confidence: 82%
“…These differences have been attributed to the specific nature of the host response and not to the virus, since vacuolization is also a characteristic feature of heterologous infections in mice (2,19,38). Mice usually do not develop any symptoms beyond 2 weeks of age, and infection of adult mice occurs without disease or histopathological lesions (7,18,43,46,61,67).…”
mentioning
confidence: 99%
“…RRV may be more stable than RRV-human reassortant viruses [10]. Alternatively, heterologous host G3 strains have been shown to replicate in mice better than non-G3 strains [11]; RRV is similar to human G3 rotavirus strains. RRV also has been shown to replicate in rabbits with greater efficiency than other heterologous host rotaviruses [12].…”
Section: Discussionmentioning
confidence: 98%